Too proactive to switch off: When taking charge drains resources and impairs detachment - Cangiano, F.; Parker, Sharon; Ouyang, K. (2021)
Although proactive behavior is an important determinant of individual work performance, its consequences for employee well-being and other personal outcomes have been largely neglected. In this study, we adopted a within-person perspective to investigate how taking charge behavior (a form of proactivity) affects employees' life outside of work by examining when and how it impacts on their ability to detach and recover from work. Drawing upon resource drain theory, we hypothesized that taking charge has the potential to undermine the process of detachment and recovery from work by draining personal resources. However, based on self-determination theory, we identified autonomous motivation as an essential boundary condition, such that the negative effects of taking charge on detachment and recovery via resource drain occur only when daily autonomous motivation is low. We tested this model on a sample of 77 managers, who provided daily survey data 3 times per day over 5 consecutive working days. Our analyses showed that daily taking charge behavior was negatively related to detachment in the evening, via resource drain, only on days in which people reported low autonomous motivation at work. However, this conditional effect of taking charge did not reach through to next morning recovery. No negative effects of daily taking charge on detachment were observed when people had high autonomous motivation. Overall, these findings suggest that, under some motivational conditions, proactivity can consume resources and interfere with the process of detachment. We offer practical advice for how organizations might encourage proactive behavior while minimizing its drawbacks. (PsycInfo Database Record (c) 2021 APA, all rights reserved).